2008
DOI: 10.1055/s-2008-1076753
|View full text |Cite
|
Sign up to set email alerts
|

The Microvascular Osteocutaneous Femur Transplant for Covering Combined Alveolar Ridge and Floor of the Mouth Defects: Preliminary Report

Abstract: In this preliminary report, the surgical technique of an oral defect coverage using the microvascular osteocutaneous flap from the distal medial femur is described and three clinical cases are reported. The new flap was used for covering combined defects of the alveolar ridge and the neighboring floor of the mouth after tumor surgery and irradiation. The bone part of the flap was supplied by the descending genicular artery and the soft tissue part by their first emission-the saphenous artery. Anastomoses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The subsequent series that have included cutaneous paddles in the flaps as part of the clinical series have relied and reported solely on use of the SAB as a blood supply to the skin paddle, with few exceptions. 4,10,13,22,23 Only 2 studies have reported some noted variation in the skin paddle arterial anatomy. One of the original descriptions by Martin et al in 1991 reported on 2 cases using this flap with skin for mandibular reconstruction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The subsequent series that have included cutaneous paddles in the flaps as part of the clinical series have relied and reported solely on use of the SAB as a blood supply to the skin paddle, with few exceptions. 4,10,13,22,23 Only 2 studies have reported some noted variation in the skin paddle arterial anatomy. One of the original descriptions by Martin et al in 1991 reported on 2 cases using this flap with skin for mandibular reconstruction.…”
Section: Discussionmentioning
confidence: 98%
“…Since its initial clinical descriptions in 1991, [3][4][5] the MFC flap has been used in a multitude of different anatomic locations to address challenging cases of nonunion or avascular necrosis. It has been successfully used in the clavicle, 6,7 humerus, 4,7-10 radius, 7,10 -12 ulna, 8,10,11,13 metacarpals, 4,14 femur, 7 tibia, 7,8,15,16 phalanges, 17 carpal and tarsal bones, 4,15,18 -21,33 orbit, 22 maxilla/ mandible, 5,23,24 and skull. 3 Despite the growing number of indications, little investigation has been focused on this flap as an osteocutaneous skin-bearing flap.…”
mentioning
confidence: 99%
“…18 Both donor sites may be used for osteocutaneous flaps. 7 The main disadvantage of the osteocutaneous radial flap is that prophylactic radius plating is necessary, 26 which is not the case when using the small femur flaps described here. 22 When prepared as a perforator flap, the skin part can be used for the inner lining of the nose.…”
Section: Discussionmentioning
confidence: 97%
“…22 When prepared as a perforator flap, the skin part can be used for the inner lining of the nose. 7 It can be thinned and harvested as a superthin flap as known for other perforator flaps. 18 The inner lining of the nose might also have been provided by a local flap 3 but a local flap from this region would have been perfused by a branch of the facial artery that had already been used as a donor vessel for the two microvascular flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation